A review of gamification tools to boost students’ motivation and engagement - Che Ku Mohd, Che Ku Nuraini; Mohamad, Siti Nurul Mahfuzah; Sulaiman, Hamzah Asyrani; Shahbodin, Faaizah; Rahim, Nur Raidah; Aizudin, Aizad (Little Lion Scientific Islamabad Pakistan, 2023)
Students today are growing up in an increasingly technology-driven world and are becoming more accustomed to using technology. They were grown using digital tools. Significant issues in adapting the learning process to students with various learning preferences must be addressed by educators. One of the educational strategies and methods that increase students' motivation and engagement is gamification. The purpose of the paper is to present and discuss the nature advantages of gamification and provide some suggestions on how to implement it in teaching and learning. In this paper, authors have listed the gamification tools that can be implemented during teaching and learning. This is important to assist the transformation of teaching and learning in higher education and preparing students for future employment in a dynamic environment highly influenced by technology and digital trends. The primary findings could be utilized as guidelines or a resource for gamification solutions to help educators and students engaged in structured learning.